Comparing knowledge management in health-care and technical support organizations. - Ghosh, B. (IEEE Transactions on information technology in biomedicine)
Although knowledge management (KM) tools are well established in technical support organizations, health-care organizations have only recently become aware of their benefits. This research investigates whether health care should adopt the same tools taking into account the different KM requirements in the two industries. This study analyzes narratives from key personnel in a technical support organization and a health-care organization to understand and compare their KM process components and facilitating information technology. The empirical data reveal that health care needs a personalization approach to KM focusing on new problem identification using interactive knowledge webs, while technical support relies on a codification approach for problem resolution using interpretive knowledge and a chain structure.